MARKEDNESS OF THEME IN EVERYTHING, EVERYTHING MOVIE DIALOG - Tarigan, Nurhayati Br; Sinar, Tengku Silvana; Harefa, Yulianus; Yusuf, Muhammad (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
This study entitled Markedness Realization in Everything, Everything Movie Script. The research is meant to analyze how the Theme markedness realized in the clauses of the movie script. The theory that is used in this research is Systemic Functional Linguistics (SFL) proposed by Halliday (1994), regarded with textual function that observes clause as a message and analyzes it from the thematic structure in the term of Theme-Rheme. He states that Theme can be divided into two, unmarked Theme is an element that occupies the point of departure position of the clause, conflating with the grammatical subject and marked Theme is an element other than occupies the point of departure position of the clause, but does not conflates with the grammatical subject. The method that is applied in this research is descriptive qualitative method. The source of data were one of the most viewed romantic movies in 2017 script, Everything, Everything, taken from Springfield Springfield site. Data of the research were selected, based on the second character dialog of this movie script. The purpose of this research is to indicate the four types of markedness and to describe the realization of the Theme markedness in the movie script. The research findings showed that the dominant type of markedness realization is simple unmarked Theme with 69.4% percentage. This type of markedness dominated other kinds of markedness realization in addition to simple marked Theme with 2.4% percentage, multiple unmarked Theme with 27.1% percentage, and multiple marked Theme with 0.9% percentage.